Cell Culture Advanced Technology and Applications in Medical and Life Sciences - Zhan, Xianquan (Biochemistry, 2022)
Cell culture is cell cloning technology that simulates in vivo environment conditions such as asepsis, appropriate temperature, and pH as well as certain nutritional conditions to enable cells to survive, grow, reproduce, and maintain their structure and function. Cell culture can be used to grow human, animal, plant, and microbial cells. Each type of cell culture has its own characteristics and essential conditions. This book focuses on the advanced technology and applications of cell culture in the research and practice of medical and life sciences. Chapters address such topics as primary cancer cell cultures, 2D and 3D cell cultures, stem cells, nanotechnology, and more.